2014
DOI: 10.1016/j.canlet.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Exploring therapeutic potentials of baicalin and its aglycone baicalein for hematological malignancies

Abstract: Despite tremendous advances in the targeted therapy for various types of hematological malignancies with successful improvements in the survival rates, emerging resistance issues are startlingly high and novel therapeutic strategies are urgently needed. In addition, chemoprevention is currently becoming an elusive goal. Plant-derived natural products have garnered considerable attention in recent years due to the potential dual functions as chemotherapeutics and dietary chemoprevention. One of the particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(62 citation statements)
references
References 60 publications
2
60
0
Order By: Relevance
“…Plant-derived natural products have garnered considerable attention in recent years due to the remarkable pharmacological properties in hematological malignancies [5,9,23]. Here, we presented the anti-leukemic effects of emodin and its combination with Ara-C on multidrug-resistant HL-60/ADR cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant-derived natural products have garnered considerable attention in recent years due to the remarkable pharmacological properties in hematological malignancies [5,9,23]. Here, we presented the anti-leukemic effects of emodin and its combination with Ara-C on multidrug-resistant HL-60/ADR cells.…”
Section: Discussionmentioning
confidence: 99%
“…HL-60/ADR cells were maintained in RPMI-1640 medium with 0.2-0.8 µg/ml ADR and were grown in ADR-free culture medium at least two weeks for each experiment. 5 /ml cells in RPMI 1640 medium with 10% fetal bovine serum were plated in 6-well plates. After 24 h of incubation with emodin, Ara-C, or emodin plus Ara-C, cells were harvested and washed with PBS, and then stained with Annexin V-PE/7-AAD (Becton Dickinson, NJ, USA) according to the manufacturer's instruction.…”
Section: Cell Lines and Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…One of the potential approaches to access better UA derivatives with improved aqueous solubility may take advantage of our published strategies by generating O -alkylamino-tethered derivatives, capable of having more favorable physicochemical properties [55-57]. Beneficial effects of making glucosides widely used in pharmaceutical industry may be another viable approach for the enhancement of solubility [58,59]. (4) Drug delivery systems are well known to improve aqueous solubility and bioavailability of many clinically used anticancer drugs [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches have shown that baicalein exerts numerous biological activities, such as anti-cancer, anti-inflammation, anti-cardiovascular diseases, anti-bacterial or viral infection, and anti-neurodegenerative diseases. Studies have demonstrated that baicalein suppresses cancer cell proliferation, induces apoptosis and cell cycle arrest in human breast, prostate, hepatocellular, myeloma and T24 bladder cancer cells (Chen et al 2014b; Li et al 2013a). Baicalein inhibits migration and invasion of human breast cancer cells, hepatoma cells and skin cancer cells (Chiu et al 2011; Wang et al 2010b; Wu et al 2011).…”
Section: Introductionmentioning
confidence: 99%